Presidential Address - Importance of edible mushrooms in Indian diet and factors responsible for low production of cultivated mushrooms - SOHI, H.S. (Indian Phytopathology, 2012)
I am thankful to members of Indian Phytopathological Society for electing me President for the year 1991. I have chosen the topic to highlight some of the factors responsible for low production of cultivated mushrooms in the country and necessary suggestions for making their culture more remunerative and economically viable under the conditions prevailing in the country.